The Effect of The Service Quality Dimension on The Satisfaction of Cu Betang Asi Cooperative Members - Leani; Lelo Sintani; Vivy Kristinae (Formosa Journal of Applied Sciences, 2023)
This study aims to determine and analyze the effect of service quality on the member satisfaction of members of CU Betang AsiCooperative in  Central Kalimantan Province. The research method is the quantitative method.   Primary and secondary data sources and data collection methods used observation, and distributing questionnaires. The sample  consisted of 250 respondents, was selected using non-probability sampling techniques through the purposive sampling method  The analytical tool is Smart-PLS Version 3.0, to test relationships in conceptual models.   Measurement reliability  based on alpha value and reliability value of Cronbach composite.  The results :  The effect of the dimensions of assurance, emphaty, responsiveness  on member satisfaction are positive and significant,  but  reliability and tangibles  on member satisfaction are negative and nonsignificant.